2018
DOI: 10.1088/1367-2630/aaa7e5
|View full text |Cite
|
Sign up to set email alerts
|

Valley-momentum locking in a graphene superlattice with Y-shaped Kekulé bond texture

Abstract: Recent experiments by Gutiérrez et al (2016 Nat. Phys. 12 950) on a graphene-copper superlattice have revealed an unusual Kekulé bond texture in the honeycomb lattice-a Y-shaped modulation of weak and strong bonds with a wave vector connecting two Dirac points. We show that this so-called 'Kek-Y' texture produces two species of massless Dirac fermions, with valley isospin locked parallel or antiparallel to the direction of motion. In a magnetic field B, the valley degeneracy of the B-dependent Landau levels is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(155 citation statements)
references
References 27 publications
0
153
2
Order By: Relevance
“…We first consider an infinite graphene nanoribbon of width W with zigzag edges and characterized by an uniform Kekulé distortion. Following Gamayun et al 22 , the nearest neighbors tight-binding Hamiltonian describing such system reads,…”
Section: Model and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first consider an infinite graphene nanoribbon of width W with zigzag edges and characterized by an uniform Kekulé distortion. Following Gamayun et al 22 , the nearest neighbors tight-binding Hamiltonian describing such system reads,…”
Section: Model and Methodsmentioning
confidence: 99%
“…For pristine graphene the hopping integral between nearest-neighbor sites t l, j = t 0 is around 2.7 eV. The Kekulé distortion of the lattice modifies the bond lengths and it is introduced through a position dependent hopping integral given by 22 ,…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A suitable mass term can now open a gap in the band structure. A recent work [49] reported that unlike the Kekule-O distortion [50], the Kekule-Y distortion does not open a gap: instead it preserves a double Dirac cone at the Brillouin zone center. Using our algorithms we identify the symmetries protecting this double Dirac cone.…”
Section: Kekule Distortion In Graphenementioning
confidence: 99%